1965
DOI: 10.1126/science.150.3696.572
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Instruction

Abstract: vegetation, that a uniform and high temperature is maintained throughout the night. Because of this fact, in the radiometric observations of tropical regions the boundaries between water and land, hence parts of the outlines of continents, cannot be distinguished.Comparison of a radiation picture of the Siberian tundra on 5 September 1964 (Fig. 16) and hydrometeorological data for the same date provides an example of very close equilibrium between soil and air temperatures. In Fig. 16 a band of clouds, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…CAI findings suggest adapting instructions to a user's current level of comprehension as well as using video, animation, and other media to improve information retention [1,6,18]. While multimedia demonstrations have been shown to increase task performance when compared to static text or verbal instructions, studies have found that demonstration information is not retained for long [16,23].…”
Section: Related Workmentioning
confidence: 91%
“…CAI findings suggest adapting instructions to a user's current level of comprehension as well as using video, animation, and other media to improve information retention [1,6,18]. While multimedia demonstrations have been shown to increase task performance when compared to static text or verbal instructions, studies have found that demonstration information is not retained for long [16,23].…”
Section: Related Workmentioning
confidence: 91%
“…Computer based tests have been used since the 1960s to test knowledge and problem solving skills 3. The earliest versions were text based and typically consisted of factual questions for which there were definite right and wrong answers.…”
Section: Where Did Computer Based Testing Come From?mentioning
confidence: 99%
“…The second category is games and simulation, where the student has some initiative but is 30 constrained by the rules of the game or the logic of the simulation. The Socratic system (Swets and Feurzeig, 1965) is a program where all possible branches in a huge tree of alternatives (with possible loops) must be specifically programmed. That tree refers to an example of some diagnostic process (medical or otherwise) which the student must perform.…”
Section: Ii1 Man-computer Interactionmentioning
confidence: 99%
“…Clearly, as we said above, they do not act on the basis of stored questions, answers, etc., but on knowledge, in the form of facts, concepts, and procedures. Also, human teachers are not pre-programmed to the ultimate detail, as is, for example, the Socratic system (Swets and Feurzeig, 1965).…”
Section: Libro: An Example Of An Advanced Afo Cai Systemmentioning
confidence: 99%